2017
DOI: 10.1177/1558944717729217
|View full text |Cite
|
Sign up to set email alerts
|

The AUSCAN and PRWHE Demonstrate Comparable Internal Consistency and Validity in Patients With Early Thumb Carpometacarpal Osteoarthritis

Abstract: The AUSCAN and PRWHE are both valid assessments for pain and/or disability in patients with early thumb CMC OA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…The Australian/Canadian Osteoarthritis Hand Index (AUSCAN) is a 15-item self-reported disease speci c questionnaire measuring pain (5-items), function (9-items) and stiffness (1-item) in the hand on a scale from 0 -none to 4 -extreme for all items. [18,20] The Patient-Rated Wrist/Hand Evaluation (PRWHE) is a self-administered questionnaire which has 2 subscales of pain (5-items) and function (10-items). The PRWHE was originally developed and tested for people with distal radius fracture (DRF) [21,23,24] and later validated as applicable to the wrist/hand for multiple conditions including arthritis as the PRWHE.…”
Section: Patient-reported Outcome Measuresmentioning
confidence: 99%
See 3 more Smart Citations
“…The Australian/Canadian Osteoarthritis Hand Index (AUSCAN) is a 15-item self-reported disease speci c questionnaire measuring pain (5-items), function (9-items) and stiffness (1-item) in the hand on a scale from 0 -none to 4 -extreme for all items. [18,20] The Patient-Rated Wrist/Hand Evaluation (PRWHE) is a self-administered questionnaire which has 2 subscales of pain (5-items) and function (10-items). The PRWHE was originally developed and tested for people with distal radius fracture (DRF) [21,23,24] and later validated as applicable to the wrist/hand for multiple conditions including arthritis as the PRWHE.…”
Section: Patient-reported Outcome Measuresmentioning
confidence: 99%
“…The PRWHE was originally developed and tested for people with distal radius fracture (DRF) [21,23,24] and later validated as applicable to the wrist/hand for multiple conditions including arthritis as the PRWHE. [18,25] Each item is scored from 0 to 10 scale which 10 indicates the worst possible pain or disability. The Thumb Disability Exam (TDX) is composed of 20 questions divided into 3 sections: hand function (11-items), pain (5-items) and satisfaction (4-items).…”
Section: Patient-reported Outcome Measuresmentioning
confidence: 99%
See 2 more Smart Citations
“…The Australian/Canadian Osteoarthritis Hand Index (AUSCAN) [18], the Patient-Rated Wrist/Hand Evaluation (PRWHE) [18] and the Thumb Disability Exam (TDX) [19] are clinical tools designed to assess pain and hand function in hand arthritis [18][19][20][21]. Both AUSCAN and PRWHE have demonstrated construct validity with verbal rating scale, had high internal consistency, and correlated with each other at baseline and follow-up time points in patients with early thumb carpometacarpal OA [18]. However, previous studies have reported inconsistent results about construct validity of AUSCAN [22][23][24].…”
Section: Introductionmentioning
confidence: 99%